PUPINIDAE OF JAVA (GASTROPODA: CAENOGASTROPODA) - Ayu Savitri Nurinsiyah; Putri Afin Nurhayati; Nova Mujiono; Alfiah Alfiah; Bernhard Hausdorf (BRIN Publishing (Penerbit BRIN), 2023)
The systematics and distribution of the family Pupinidae (Gastropoda: Cyclophoroidea) in Java is reviewed. The family is represented in Java by four species of the genus Pupina, P. bipalatalis, P. compacta, P. junghuhni, and P. treubi. The shells of the species are described and figured, and the distribution data of the species are summarized. We have synonymized Pupina verbeeki Möllendorff, 1897 with Pupina treubi Boettger, 1890. All of the species except P. treubi, which is also known from Sumatra, are endemic to Java. Most previous records of Pupina from Java were from the western part of the island. Our new records show that the Pupina species are also more widespread in the drier central and eastern parts of Java. Their conservation status is therefore Least Concern.